Programa de universalização de energia elétrica: estudo de caso no Estado da Bahia - Heidorn, Guilherme Azevedo (2009)
This study is related to the development of the electricity services universalization process in Brazil. It describes the former model, the first universalization proposals, a legislation evolution since the beginning in 2002, its adaptation to the current situation among the country to the electric-power distribution companies, to costumers and to the concessions areas. Its first objective is to analyze the results achieved from the universalization process until 2008, focusing as a Case Study The Bahia State Universalization Program. The state of Bahia, according to the 2000 Brazilian Institute of Geography and Statistics (IBGE) national census, presented the highest quantity of rural households without access to electricity services in Brazil. Moreover, it has a vast territorial extension, a spread market to be served and basically low income costumers. Then, it shows long and high-cost network extensions to reach low demands. As a result, the universalization program in Bahia is highly representative comparing with the whole Brazilian Program